Electric Power Systems and Networks электронный курс - Fix, N. P. specialist in the field of electrical engineering Associate Professor of Tomsk Polytechnic University, candidate of pedagogical sciences 1971- (TPU Moodle, 2020)
Course objectives: training students in knowledge of technical processes, electrical networks, power engineering equipment, understanding of technical processes, analyzing modes of systems and networks by special engineering software, constructing models of power systems and networks, obtaining skills in designing of power networks. This course belongs to the professional cycle and introduces the standards and vocabulary used in the electric utility industry. Students will learn about the segments and common components of the electric power system. The course is a combination of online activities and face-to-face communication. The content of the course includes laboratory practical, practical problems, course project and theoretical background.